Development of a self-administered early inflammatory arthritis detection tool - Bell, Mary J; Tavares, Ruben; Guillemin, Francis; Bykerk, Vivian P; Tugwell, Peter; Wells, George A (Université d'Ottawa | University of Ottawa, 2010)
Abstract Background Barriers to care limit the potential benefits of pharmacological intervention for inflammatory arthritis. A self-administered questionnaire for early inflammatory arthritis (EIA) detection may complement contemporary triage interventions to further reduce delays to rheumatologic care. The objective of this study was to develop a self-administered EIA detection tool for implementation in pre-primary care settings. Methods A core set of dimensions and constructs for EIA detection were systematically derived from the literature and augmented by investigative team arbitration. Identified constructs were formulated into lay language questions suitable for self-administration. A three-round Delphi consensus panel of EIA experts and stakeholders evaluated the relevance of each question to EIA detection and suggested additional items. Questions accepted by less than 70% of respondents in rounds one or two were eliminated. In round three, questions accepted by at least 80% of the panel were selected for the tool. Results Of 584 citations identified, data were extracted from 47 eligible articles. Upon arbitration of the literature synthesis, 30 constructs encompassing 13 dimensions were formulated into lay language questions and posed to the Delphi panel. A total of 181 EIA experts and stakeholders participated on the Delphi panel: round one, 60; round two, 59; and, round three, 169; 48 participated in all three rounds. The panel evaluated the 30 questions derived from the literature synthesis, suggested five additional items, and eliminated a total of 24. The eleven-question instrument developed captured dimensions of articular pain, swelling, and stiffness, distribution of joint involvement, function, and diagnostic and family history. Conclusions An eleven-question, EIA detection tool suitable for self-administration was developed to screen subjects with six to 52 weeks of musculoskeletal complaints. Psychometric and performance property testing of the tool is ongoing.